PERBANDINGAN PEWARNA ALAMI KUNYIT DAN HENNA TERHADAP HASIL PEWARNAAN RAMBUT - ELVA APRILIA; Merita Yanita (Jurnal Tata Rias dan Kecantikan, 2022)
The results of the practice of dyeing hair using natural ingredients make hair not fall out easily, reducing hair damage due to the use of chemical hair dyes. This study aims to a) analyze the results of hair coloring using turmeric natural dyes, b) to analyze the effect of the results of hair coloring using artificial henna dyes and c) to analyze the comparison of the results of hair coloring using turmeric natural dyes and artificial henna dyes.This type of research is experiment. The population of this study was the 2016 Padang State University student with 2 samples and 7 panelists. The data collection technique was purposive sampling method. Descriptive data analysis techniques by displaying statistics and frequency. Bivariate analysis using independent sample-t-test with 95% confidence. Based on the results of the study, the use of natural turmeric dyes from the color aspect an average of 3.42 categories is very clear and the color absorption time aspect is an average of 4 categories 30 minutes In the use of artificial henna dyes, from the color aspect an average of 2.85 clear categories and an average color absorption time aspect of 2.57 categories 50 minutes and there was no difference in the effect of the results of hair coloring using turmeric natural dyes and artificial henna dyes. P value = 0.091 (p> 0.05). There are differences in the effect of the results of hair coloring using turmeric and artificial henna dyes. P value = 0.026 (p <0.05).The conclusion is that there is no difference in the effect of the results of hair coloring using natural turmeric dyes and artificial henna dyes and there are differences in the effects of hair coloring using turmeric natural dyes and artificial henna dyes and it is recommended for all makeup and beauty students who are undergoing lectures in order to produce results. This study is one of the references in using the natural color of turmeric in hair coloring practices.